Clinical trial of two antivenoms for the treatment of Bothrops and Lachesis bites in the north eastern Amazon region of Brazil. - Pardal, P; Souza, S; Monteiro, MR; Fan, H; Cardoso, J; França, F; Tomy, S; Sano-Martins, I; Sousa-e-Silva, d; Colombini, M; Kodera, N; Moura-da-Silva, A; et al. (2004)
The efficacies of specific Bothrops atrox-Lachesis and standard Bothrops-Lachesis antivenoms were compared in the north eastern Amazon region of Brazil. The main aim was to investigate whether a specific antivenom raised against the venom of B. atrox, the most important Amazon snake species from a medical point of view, was necessary for the treatment of patients in this region. Seventy-four patients with local and systemic effects of envenoming by Bothrops or Lachesis snakes were randomly allocated to receive either specific (n = 38) or standard (n = 36) antivenoms. In 46 cases (24 in the standard antivenom group, 22 in the other) the snake was identified either by enzyme immunoassay or by examination of the dead snake, as B. atrox in 45, L. muta in one. Patients were similar in all clinical and epidemiological respects before treatment. Results indicated that both antivenoms were equally effective in reversing all signs of envenoming detected both clinically and in the laboratory. Venom-induced haemostatic abnormalities were resolved within 24 h after the start of antivenom therapy in most patients. The extent of local complications, such as local skin necrosis and secondary infection, was similar in both groups. There were no deaths. The incidence of early anaphylactic reactions was 18% and 19%, respectively for specific and standard antivenoms; none was life-threatening. Measurement of serum venom concentrations by enzyme immunoassay (EIA) confirmed that both antivenoms cleared venom antigenaemia effectively. EIA also revealed that one patient had been bitten by Lachesis muta, although the clinical features in this case were not distinctive.